The analysis new product development process of kale commodities in Gumuk Bago Nogosari Village Rambipuji - Pratiwi, Puput; Cahyaningrum, Deltaningtyas Tri (Universitas Musamus, Merauke, Papua, 2025)
New Product Development (NPD) process is a structured step to turn a concept into a market-ready product. One of the products that has great potential is kale, which is widely found in Gumuk Bago Hamlet, Nogosari Village, Rambipuji, Jember Regency. This research aims to develop kale noodles to improve the quality of kale commodities and provide added value for local farmers. The approach used is qualitative descriptive with data collection through interviews, observations, and literature studies involving 20 local farmers. The NPD process of kale noodles involves making kale flour through drying at a temperature of 50° C to maintain the nutrient content, then formulated with wheat flour at a ratio of 20%. The results of the study showed that kale noodles have a higher fiber and iron content than conventional noodles, so they have health benefits, such as preventing anemia and improving digestion. Organoleptic tests show that kale noodles are preferred by consumers because of their balanced taste, chewy texture, and attractive appearance. Processing kale into flour also helps reduce farmers' losses due to wasted crops and increase their income. The market projection in Jember Regency is estimated to reach Rp 2.5 billion a year. However, there are several weaknesses, such as limited processing technology, inadequate distribution infrastructure, limited marketing, seasonal dependence on raw materials, and low brand awareness that can hinder market penetration. With the right handling of these weaknesses, the development of kale noodles has the potential to strengthen the local economy and improve the welfare of farmers.